Sikap Perawat Dengan Pelaksanaan Identifikasi Pasien di Ruang Rawat Inap RSUD Indrasari - Mayenti, Fitra; Meri, Dilgu; Deswita, Deswita; Apitri, Triliza; Yulianto, Yulianto (Universitas Fort De Kock Bukittinggi, 2024)
Backgroound:Patient safety is a basic principle of health care in health institutions that continues to require quality improvement. Accurate patient identification is important, even in relation to patient safety. Patient identification is a very basic thing that must be done by a nurse. Correct patient identification can avoid medical errors or unexpected events that could affect the patient. The importance of patient identification is strongly supported by the attitude of a nurse. This study aims to analyze the relationship between nurses' attitudes and the implementation of patient identification in the inpatient room at Indrasari Regional General Hospital. Methods: This research design is descriptive with a cross sectional approach. The number of samples in this study was 79 people with the sampling technique used was Probability Sampling with Proportionate Stratified random sampling. This research instrument uses a questionnaire. Data were analyzed univariately and bivariately with the Pearson chi-square test. Results: Result of this research is majority of patient identification attitudes were in the positive category, with as many as 59 respondents (74.7and mostly in the negative category, with as many as 20 respondents (25.3%). There is a relationship between nurses' attitudes and the implementation of patient identification in the inpatient ward at Indrasari General Hospital with a p value of 0.000. Conclusion: It is recommended that nurses carry out training and update their knowledge on ways to improve the implementation of patient identification, so that they can increase nurses' knowledge regarding the implementation of patient identification.